Analiza i ocena technik kreatywnych wykorzystywanych w krajowej reklamie prasowej - Woźniczka, Jarosław (The Analysis and Assessment of Creative Execution Formats Used in Domestic Press Advertising, 2007)
The article presents results of an analysis of 250 domestic press advertisements. The main focus was on the most common creative formats used in the advertising. The analysis is a part of a bigger research project on creative planning in domestic press advertising. As a result of the analysis, a dozen or so creative planning in domestic press advertising. As a result of the analysis, a dozen or so creative formats were identified and the characterized. Afterwards, an analysis of the frequency of each format in sample was earned out, followed by identifying relations between a type of format and categories of products being advertised. It was also noted how many advertisements use single or multiple creative formats.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Marketing (3); 2007; nr 1171, s. 65-74